2019
DOI: 10.1155/2019/9083068
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Nanotechnology in the Codelivery of Active Constituents of Plants and Chemotherapeutics for Overcoming Physiological Barriers during Antitumor Treatment

Abstract: Antitumor therapy using a combination of drugs has shown increased clinical efficacy. Active constituents derived from plants can offer several advantages, such as high efficiacy, low toxicity, extensive effects, and multiple targets. At present, the combination of plants’ active constituents and chemotherapeutic drugs has attracted increased attention. Nanodrug delivery systems (NDDSs) have been widely used in tumor-targeted therapy because of their efficacy of delivering antitumor drugs. The in vivo process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 150 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…25 It was previously demonstrated that combination of active plant ingredients with first-line chemotherapy drugs has shown good efficacy in reversing tumor chemoresistance, enhancing curative effects, and reducing adverse reactions. 36…”
Section: Resultsmentioning
confidence: 99%
“…25 It was previously demonstrated that combination of active plant ingredients with first-line chemotherapy drugs has shown good efficacy in reversing tumor chemoresistance, enhancing curative effects, and reducing adverse reactions. 36…”
Section: Resultsmentioning
confidence: 99%
“…However, many active components in TCM, such as chemical drugs, exhibit several drawbacks, including limited solubility and low bioavailability [ 111 113 ]. Many investigations have found that active components from TCM and chemical drugs self-assemble to generate nanopreparations [ 114 ]. This self-assembly technique increases the solubility and bioavailability of the two drugs, plays a synergistic function, and reduces the negative effects of chemical drugs.…”
Section: The Self-assembly Forms Of Csanmentioning
confidence: 99%
“…In addition, damage to the lymphatic system in tumor tissues inhibits the re-entry of components into blood circulation, thus allowing them to remain in tumor tissues. The EPR effect promotes the high accumulation of nanoformulations in tumor tissues (compared to normal tissues), reduces the side effects of chemotherapy drugs, and provides a good opportunity for the treatment of cancer with nanoformulations ( Li Q. et al, 2019 ; Kalyane et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%